2006
DOI: 10.1016/j.mssp.2006.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium oxide thin films deposited by high pressure reactive sputtering in atmosphere formed with different Ar/O2 ratios

Abstract: The physical and electrical properties of hafnium oxide (HfO 2 ) thin films deposited by high pressure reactive sputtering (HPRS) have been studied as a function of the Ar/O 2 ratio in the sputtering gas mixture. Transmission electron microscopy shows that the HfO 2 films are polycrystalline, except the films deposited in pure Ar, which are amorphous. According to heavy ion elastic recoil detection analysis, the films deposited without using O 2 are stoichiometric, which means that the composition of the HfO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…The peak at 748 cm -1 has also been studied previously and assigned to an A u mode (atomic displacement parallel to the c axis of the unit-cell) [22]. As can be seen in Figure 2 both peaks disappear in the sample deposited with pure Ar plasma, while they are present in the sample deposited with O 2 or mixed O 2 /Ar plasmas [32]. This is in agreement with previous reports [23,40] that showed only a broad band starting at 500 cm -1 and extending into the far infrared region for amorphous hafnium oxide.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The peak at 748 cm -1 has also been studied previously and assigned to an A u mode (atomic displacement parallel to the c axis of the unit-cell) [22]. As can be seen in Figure 2 both peaks disappear in the sample deposited with pure Ar plasma, while they are present in the sample deposited with O 2 or mixed O 2 /Ar plasmas [32]. This is in agreement with previous reports [23,40] that showed only a broad band starting at 500 cm -1 and extending into the far infrared region for amorphous hafnium oxide.…”
Section: Resultsmentioning
confidence: 61%
“…In a previous work we showed that mixed O 2 /Ar plasmas with different gas flow ratios always formed films with a polycrystalline structure [32]. So, it is necessary to eliminate completely the presence of O 2 to obtain amorphous films.…”
Section: Resultsmentioning
confidence: 98%
“…Previous works of our group showed that HfO 2 films deposited with Ar plasma were amorphous whereas deposited films with plasmas of O 2 or different Ar/ O 2 ratios were polycrystalline. 29 This will be the subject of future work.…”
Section: Resultsmentioning
confidence: 97%
“…At lower wave numbers, the known HfO 2 bands were found. 3 The well-known asymmetric stretching vibration of the SiN absorption band between 750 and 970 cm −1 is observed in the SiN layer prior to the deposition of HfO 2 . The maximum of the band is placed at 844 cm −1 , slightly above the frea͒ Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…The bonding structure changes of this SiN layer were studied after the HfO 2 sputtering in both pure Ar and pure O 2 plasmas, which were previously found to produce amorphous or polycrystalline HfO 2 of monoclinic phase, respectively, as well as an interfacial silicon oxide layer. 3 Glow discharge optical spectroscopy ͑GDOS͒ is a powerful technique to analyze the composition of plasmas. 4 In this letter, this technique was used to understand the origin of the oxidation mechanism and the structural changes of the SiN buffer layer that occur during the HfO 2 sputtering.…”
mentioning
confidence: 99%